2000
DOI: 10.1097/00000542-200009000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Physostigmine Reverses Propofol-induced Unconsciousness and Attenuation of the Auditory Steady State Response and Bispectral Index in Human Volunteers

Abstract: These findings suggest that the unconsciousness produced by propofol is mediated at least in part via interruption of central cholinergic muscarinic transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 39 publications
3
93
0
1
Order By: Relevance
“…Physostigmine, widely used in the treatment of the central anticholinergic syndrome, is also effective in preventing and treating behavioural disturbances following propofol anaesthesia [28,29]. Physostigmine is effective in treating cerebellar ataxia [30] and reduced centrally mediated muscular hyperactivity, perhaps inhibiting the fraction of postanaesthetic shivering that resembles clonus [16].…”
Section: Discussionmentioning
confidence: 99%
“…Physostigmine, widely used in the treatment of the central anticholinergic syndrome, is also effective in preventing and treating behavioural disturbances following propofol anaesthesia [28,29]. Physostigmine is effective in treating cerebellar ataxia [30] and reduced centrally mediated muscular hyperactivity, perhaps inhibiting the fraction of postanaesthetic shivering that resembles clonus [16].…”
Section: Discussionmentioning
confidence: 99%
“…VTA projections to the cortex induce superficial layer cortical postsynaptic depolarizations (41), which is consistent with the loss of coherence we observed in superficial layers of cortex at preROM. A number of other investigations have reported cholinergic (42)(43)(44) and dopaminergic (45,46) influences on arousal that provoke recovery of consciousness after anesthesia-induced unconsciousness. Our work, alongside this evidence from previous studies, suggests that the "hysteresis" during emergence from anesthesiainduced unconsciousness (29) could be explained by active enhancement of arousal from the basal forebrain and VTA.…”
Section: Discussionmentioning
confidence: 98%
“…The results are generally consistent with previous studies. Increasing central Ach levels is known to reduce the depth of anesthesia (Meuret et al, 2000;Hudetz et al, 2003). Laalou et al (2008) reported that NBM lesion with 192IgG-saporin increased the anesthetic, but not the subanesthetic, effects of cumulative doses of propofol (i.p.).…”
Section: Correlation Of Averagementioning
confidence: 99%
“…An anticholinesterase that increased central Ach levels was shown to reduce the depth of anesthesia induced by propofol or isoflurane (Meuret et al, 2000;Hudetz et al, 2003). Pain et al (2000) reported that central Ach depletion by intracerebroventricular (icv) administration of 192IgG-saporin reduced the sedative potency of low-dose (30 mg/kg i.p.)…”
Section: Introductionmentioning
confidence: 99%